2016
DOI: 10.1136/jech-2016-207588
|View full text |Cite
|
Sign up to set email alerts
|

Glycated haemoglobin (HbA1c), diabetes and trajectories of change in episodic memory performance

Abstract: Higher HbA1c and diabetes were both associated with declines in episodic memory, with this relationship further exacerbated by having diabetes and elevated HbA1c. HbA1c appeared more important for episodic memory performance among women than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
5
15
0
Order By: Relevance
“…Consistent with our MEG/HbA 1c correlation findings, previous behavioral studies have linked deficits in working memory processing with glycemic control (35). For example, intensive regulation of glycemic control in adolescents with type 1 diabetes (36) and adults with type 2 diabetes (37) has been shown to improve working memory task performance, although there is also a risk of increased hypoglycemic episodes with intensive treatment regimens, which may again lead to worse cognitive outcomes long-term (6,37).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our MEG/HbA 1c correlation findings, previous behavioral studies have linked deficits in working memory processing with glycemic control (35). For example, intensive regulation of glycemic control in adolescents with type 1 diabetes (36) and adults with type 2 diabetes (37) has been shown to improve working memory task performance, although there is also a risk of increased hypoglycemic episodes with intensive treatment regimens, which may again lead to worse cognitive outcomes long-term (6,37).…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with a previous systematic review by Geijselaers et al, in which HbA1c accounted for less than 10% of variance in cognition in subjects with type 2 diabetes . The strongest associations were observed in postmenopausal women with obesity, supporting a previous study with older adults in which Hb1Ac appeared more important for episodic memory performance among women than among men .…”
Section: Discussionsupporting
confidence: 92%
“…The non-significant results in our study for the global cognitive score may be explained by its derivation from a wider range of tests than used in other studies: some of the tests used showed less decline in type 2 diabetes (described further below) and hence a cancelling of effects. Studies in older age have also reported mixed results for specific cognitive domains: some have reported greater decline in verbal fluency [38] and memory [37,39] in people with type 2 diabetes, whereas several others have reported no differences [5,9,34,35,38,40]. These mixed findings most likely reflect differences in populations, follow-up times and cognitive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies commencing in midlife and followed up over 10 years or more tend to show that type 2 diabetes is associated with faster decline in global cognitive function [3,6], processing speed [4,6], executive function [3,4], verbal fluency [6] and memory [3,4,6]. However, in older cohorts, these associations are more variable, with some showing greater decline in global cognition [5,[34][35][36], but not others [8,9,37]. The non-significant results in our study for the global cognitive score may be explained by its derivation from a wider range of tests than used in other studies: some of the tests used showed less decline in type 2 diabetes (described further below) and hence a cancelling of effects.…”
Section: Discussionmentioning
confidence: 99%